Evaluation of the Economic Feasibility and Development Decision for Al-Haji Al-Baree Route within the Bahr Al-Najaf Region - Al-Helaly, Mustafa Hasan; Alfadhel, Ali Abdulhussaein Khaleel; Al-Jameel, Hamid Athab; Rahi, Mohamed Ghali (Journal of Ecohumanism, 2024)
Roads are an economic and development indicator, and the development and multiplicity of roads mean that cities with high sustainable development and vice versa, often have economic and social prosperity. This study focused on two axes, the first is the development potential provided by the development of the Najaf Haji road, the second is an assessment of the reality and economic feasibility of the development decision for this road, which is undergoing deterioration and has been flooded by Bahar Al- Najaf in the last five years. It leads to the prosperity of growth resulting from the area surrounding Najaf, as well as to the city of Najaf in general, as the area turns into a recreational park for tourists to the city of Najaf and neighboring cities for visitors to the holy city. The results demonstrate that a very positive impact was found for both technical impact analysis, social impact analysis, and project idea the project. Whereas, project risk analysis, project sector development analysis, and environmental impact analysis represent the positive impact on the project development